Control of the domain of multiple filamentation of terawatt laser pulses along a hundred-meter air path. (31st May 2015) - Apeksimov, D V; Geints, Yu E; Zemlyanov, A A; Kabanov, A M; Matvienko, G G; Oshlakov, V K
Abstract We report the results of experiments and numerical simulation for multiple filamentation of terawatt femtosecond pulses of a Ti : sapphire laser on a 106-meter long air path under varied initial spatial focusing and laser output power. Highly efficient control of the position and length of the filamentation domain is realised by varying the initial focusing of the laser beam, which provides the movement of the filamentation domain along the entire optical path. The unimodal character of the distribution of the number of plasma channels formed by the laser beam along the optical path is revealed and a correlation of the coordinates corresponding to the maximal number of plasma channels and to the nonlinear focus of the beam as a whole is established.